Are split liver grafts a suitable option in high-risk liver transplant recipients?. Issue 6 (December 2021) - Lau, Ngee-Soon; Liu, Ken; McCaughan, Geoffrey; Crawford, Michael; Pulitano, Carlo
Abstract : Purpose of review: To assess the outcomes of split liver transplantation (SLT) in adults and children and evaluate its role in high-risk recipients with a high model for end-stage liver disease (MELD) score, an urgent indication or requiring retransplantation. Recent findings: Split liver grafts in general have equivalent long-term survival outcomes to whole grafts despite an increase in biliary complications. Recent success and technical advances have encouraged use of these grafts in high-risk recipients. Split liver grafts can be used successfully in recipients with a high MELD score if there is adequate weight-matching. There are mixed results in urgent indication recipients and for retransplantation such that use in this group of patients remains controversial. Summary: SLT addresses donor shortages by facilitating the transplant of two recipients from the same donor liver. By using careful donor and recipient selection criteria, SLT can achieve equivalent long-term outcomes to whole grafts. These grafts have been used successfully in recipients with a high MELD score, but should be used selectively in urgent indication recipients and for retransplantation. Abstract : Supplemental Digital Content is available in the text